Rice Production and Food Poverty Vulnerability in North Sulawesi - Maya Hendrietta Montolalu; Ellen Grace Tangkere; David P. Rumambi; Putri Septiani Narwastu Tangka (Postgraduate, University of Mataram, 2026)
Food security remains a major challenge in developing countries, particularly in relation to the vulnerability of food consumption among low-income households. Rice plays a central role in Indonesia’s food system as the main staple food and a key determinant of food availability and access. However, increasing rice production does not necessarily guarantee adequate food consumption if economic access to food remains limited. This study aims to analyze the relationship between rice production, food access factors, and the prevalence of food consumption inadequacy as an indicator of food poverty vulnerability. The analysis employs a Two-Stage Least Squares (2SLS) econometric approach using secondary data from the Indonesian Central Bureau of Statistics and related institutions for the period 2018–2023. The first-stage estimation shows that paddy harvested area is the most significant factor influencing rice production, highlighting the importance of land utilization in determining food availability. In the second stage, the number of poor population emerges as the most influential factor affecting food consumption inadequacy, while income per capita and average rice production contribute to reducing the prevalence of inadequate food consumption. These findings indicate that food insecurity is driven not only by the availability of staple food but also by households’ economic ability to access food. Therefore, strengthening food security requires integrated policies that simultaneously support agricultural production, protect agricultural land, and reduce poverty to improve household access to food